Ultra Wideband Radar for Respiratory Monitoring on Sleep Position - Nurul Qashri Mahardika T; Erfansyah Ali; Fiky Yosef Suratman (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2021)
Sleep apnea is a sleep disorder that has a relation with respiratory system during sleep.One of the sleep apnea characteristic is suddenly stop breathing during sleep. Peoplehave the dierent of respiratory rate (RR) which is affected by sleep positions andbody mass index (BMI).There are four sleep positions aecting the respiratory rate(RR). Polysomnography (PSG) is conventionally used to analysis the sleep apnea. Thistechnique requires body contact that might be uncomfortable for the patient. In thisstudy, the Xethru X4M200 radar sensor is proposed as non-contact tool to detect the RRby implementing the Doppler effect. Furthermore, the relation between RR with the sleepposition and the BMI are discused. For that purpose, 20 participants (10 males and 10females) with dierent BMIs and sleep positions are examined by monitoring their chestmovement. This method is able to detect the indication of bradypnoea or tachypnoea.Futher systematic study and more participants are required to confirm our results andprovide better non-contact technique for RR measurement.